UJI AKTIVITAS ANTIJAMUR EKSTRAK KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) TERHADAP PERTUMBUHAN JAMUR TRICHOPHYTON RUBRUM SECARA IN VITRO - Yuliawati Banjar Nahor, (2021)
The high prevalence of superficial mycoses associated with antifungal drug resistance. That resistance can be overcome with utilizing the active compounds contained in a plant. Red dragon fruit peel has the potency as an antifungal agent because it contains high levels of phenolic and flavonoids. This study aimed to examine the antifungal effect from ethanol extract of red dragon fruit peel against Trichophyton rubrum with well diffusion method. The extract concentration consisted from 12.5%, 25%, 50%, 100% and the control group consisted ketokonazole and aquades. Kruskal-Wallis and Mann-Whitney test were used to compare the antifungal activity. The result showed that the red dragon fruit peel could inhibit the growth of T. rubrum fungus. The extract concentration of 12.5% produced the smallest inhibition zone and 100% produced the widest inhibition zone. Kruskal-Wallis test showed sig. <0.005 that meant the antifungal test group had a significant difference. The Mann-Whitney test showed sig. <0.05 that meant there were significant differences between the two groups except at a concentration of 25% toward a concentration of 12.5% and 50%. The antifungal mechanism of red dragon fruit peel extract is fungistatic and effective in inhibiting the growth of T. rubrum.